The Role and Challenges of Plastic Surgery in Post-burn Psychological Rehabilitation - Yu, Liming; Guo, Ruiyu; Zhang, Meiying (Journal of Contemporary Medical Practice, 2025)
Burns, a traumatic illness with a high disability rate, often have profound physiological and psychological impacts on patients. With the shift in medical paradigms, psychological rehabilitation has become an integral part of burn care. Plastic surgery not only plays a crucial role in restoring appearance and function in burn rehabilitation but also plays a crucial role in the patient’s psychological reconstruction. This article discusses the role and challenges of plastic surgery in post-burn psychological rehabilitation, highlighting its positive contributions to appearance restoration, self-identity restoration, functional improvement, and doctor-patient communication. It also analyzes practical challenges, such as the blurred boundaries between medicine and psychology, the gap between patient expectations and reality, the social stigma associated with scars, and resource and institutional constraints. To enhance the depth of plastic surgery’s involvement in psychological rehabilitation, this article proposes strategies such as establishing a collaborative mechanism between plastic surgery and psychology, introducing standardized psychological assessment tools and intervention processes, strengthening physician psychological communication training, building a social support system, and conducting integrated clinical research. The study concludes that plastic surgery holds irreplaceable value in post-burn psychological rehabilitation and that its deep integration with psychological rehabilitation should be promoted in the future to achieve both physical and psychological rehabilitation for patients and comprehensively enhance the quality of burn rehabilitation and the level of humanistic care.